Cytotoxicity and concentration of silver ions released from dressings in the treatment of infected wounds: a systematic review - Sánchez-Gálvez, Javier; Martínez-Isasi, Santiago; Gómez-Salgado, Juan; Rumbo-Prieto, José María; Sobrido-Prieto, María; Sánchez-Hernández, Miriam; García-Martínez, María; Fernández-García, Daniel (Frontiers in Public Health, 2024)
Introduction Silver-releasing dressings are used in the treatment of infected wounds. Despite their widespread use, neither the amount of silver released nor the potential in vivo toxicity is known. The aim of this study was to evaluate the cytotoxic effects and the amount of silver released from commercially available dressings with infected wounds. Methods The review was conducted according to the PRISMA statement. The Web of Science, PubMed, Embase, Scopus, and CINAHL databases were searched for studies from 2002 through December 2022. The criteria were as follows: population (human patients with infected wounds); intervention (commercial dressings with clinical silver authorized for use in humans); and outcomes (concentrations of silver ions released into tissues and plasma). Any study based on silver-free dressings, experimental dressings, or dressings not for clinical use in humans should be excluded. According to the type of study, systematic reviews, experimental, quasi-experimental, and observational studies in English, Spanish, or Portuguese were considered. The quality of the selected studies was assessed using the JBI critical appraisal tools. Studies that assessed at least 65% of the included items were included. Data were extracted independently by two reviewers. Results 740 articles were found and five were finally selected (all of them quasi-experimental). Heterogeneity was found in terms of study design, application of silver dressings, and methods of assessment, which limited the comparability between studies. Conclusion In vivo comparative studies of clinical dressings for control of infection lack a standardized methodology that allows observation of all the variables of silver performance at local and systemic levels, as well as evaluation of its cytotoxicity. It cannot be concluded whether the assessed concentrations of released silver in commercial dressings for the topical treatment of infected wounds are cytotoxic to skin cells. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022351041, PROSPERO [CRD42022351041].